Design and Build Academic Website with Digital Certificate Storage Using Blockchain Technology - A. Faaroek, Safiani; Saulina Panjaitan, Aropria; Fauziah, Zaleha; Septiani, Nanda (Pandawan Sejahtera Indonesia, 2022)
A certificate is a form of award that is obtained by someone after completing a competency test or certain learning. Certificates must be generated and stored in a safe and secure manner to prevent alteration of content or even falsification. Blockchain technology is a technology that allows secure storage processes at low costs. Security is guaranteed because everyone can take part in storing data with a distributed ledger. Based on the results of research and system design, it can be concluded that the process of making blockchain technology as a medium for issuing certificates and their validation can be made using Ethereum's program, namely Geth, and storing data using smart contracts issued on the blockchain network. The results of the reliability testing of the system show that the system has successfully processed 200 transactions in approximately 8 seconds. For scalability testing, it is estimated that 10 million blocks require a storage capacity of 22.6 GB to become a node or miner on this blockchain network.